Current treatment of visceral leishmaniasis (Kala-azar): an overview - Singh, Premshanker S.; Kumar, Manoj (International Journal of Research in Medical Sciences, 2017)
Visceral Leishmaniasis (VL) is also popularly known as kala-azar which was first reported in early forties and since then it continues to affect millions of people. The ranges of common drugs available for the treatment of visceral leishmaniasis are limited. It mainly includes pentavalent antimonials e.g. stibogluconate (SbV), amphotericin B deoxycholate (AB), lipid formulations of amphotericin B (L-AB), miltefosine (MF) and paromomycin (PM) - all of which have limitations in terms of toxicity, variable efficacy, price and inconvenient treatment schedules. Most are parenteral except MF which is administered orally. Due to the parasite’s drug resistance, the most widely used (SbV) of these drugs is now of little use in northern Bihar, India, which alone accounts for 50% of the world’s burden of visceral leishmaniasis. In areas of resistance to SbV, AB is highly effective. The formulation of AB in liposomes (L-AB) has been a major advancement in the treatment of visceral leishmaniasis. However, despite a significant reduction in price, this treatment remains very expensive for endemic countries like India. Combination short course therapy has been reported by many researchers who found that it is equally effective as conventional monotherapy with added benefits of less side effects, better compliance and less resistance. The aim of this article is to review the current aspects of the treatment for leishmaniasis, giving an overview of current agents clinically used to new agents & modalities of treatment under development.